THU0251 Effectiveness of Conventional Dmards Using a Treat to Target Strategy in the Context of a Large Cohort of Rheumatoid Arthritis Patients. (23rd January 2014) - Santos-Moreno, P.; Sandoval, C.; Villarreal, L.; Real, A. P.; Boon, P.; Palomino, A.; Urbina, A.; Bello, J.
Abstract : Background: The importance of early effective therapy, implications of disease activity in progression and use of composite disease activity measures in rheumatoid arthritis (RA), led to developing of defined therapeutic targets and tools to achieve them resulting in the Treat to Target (T2T) initiative. This strategy is being used last 2 years in Colombia in a specialized in RA center. Objectives: The aim of this study was to describe general change in Disease Activity Score 28 (DAS28) using A T2T strategy during a 24 month period in a large cohort of RA patients treated with conventional DMARDs. Methods: A descriptive cross-sectional study was performed. Patients from a rheumatologic center with diagnosis of RA (ACR 1987 and 2010 ACR/EULAR criteria) were assessed applying a T2T strategy. A standardized follow-up was designed using DAS28: every 3-5 weeks (DAS28 > 5.1), every 7-9 weeks (DAS28 ≥ 3.2 and ≤ 5.1), and every 11-13 weeks (DAS28 < 3.2). It was measured tender joint counts, swollen joint counts, DAS28 and HAQ at every visit. In case of DAS28 > 3.2 it was mandatory to introduce adjustments in treatment based on a predetermined clinical guideline. Were included patients who seen at least 6 times their doctor. We calculated percentages and averages from this data and divided patients in two groups: remission-low disease activity (Rem/LDA) patients and moderate-severe disease activity (MDA/SDA) patients. Global change in DAS28, joint counts and HAQ was determined at beginning, 6, 12, 18 and 24 months and assessed using Chi-square test. Results: 1321 patients were included in this study, 1026 (77.7%) women and 295 (22.3%) men. All patients had established disease (more than 2 years of duration) and average age 60.1 y/o. Regarding the entire cohort, majority of patients were using DMARDs in combination, 63% of patients were using methotrexate, 30.2% of patients sulfasalazine, 23.6% of patients leflunomide, 19% of patients and prednisolone 45.3%. At initial visit, we found only 47% patients in Rem-LDA activity and 53% patients in MDA/SDA activity according to DAS28. At 6, 12, 18 and 24 months we found improvement to 63%, 70%, 74% and 84% respectively in patients of Rem/LDA group. On the other hand was observed a decrease on proportions of patients in MDA/SDA group. The difference of medians for each variable showed improvement with statistical significance (p < 0.00). It was not established improvement in HAQ. Conclusions: This study shows general improvement of DAS28 in RA patients treated with conventional DMARDs and applying a T2T strategy; it was found a globally increase in the percentage of patients in Rem-LDA activity group and decrease in MDA/SDA group. Standard T2T follow-up in patients with RA should be done based on: correct use of disease activity scores and visits/treatment decisions based on, and was proved that achieving remission/LDA using only conventional DMARDs is a realistic goal in clinical practice. Disclosure of Interest: None Declared